Partnership management of the vocational school and business / industrial world in achieving graduate quality - Yurnalissa Yurnalissa; Siti Maria (Jurnal Taman Vokasi, 2019)
This is study aims at describing vocational partnership management with World ofEnterprises and Industry in achieving vocational school’s graduates including (a) planning, (b)organizing, (c) actuating, (d) controlling and its support and obstacles in Fishery ProcessingTechnology Department of vocational school 1 Sanden Bantul. This study is qualitative research inFishery Processing Technology Department of vocational school 1 Sanden Bantul as the setting. Thedata sources in this research are : (1) informants, including the school principal, vice-principal ofcurriculum, vice-principal of public relation, vice-principal of infrastructure, counseling teacher, themanager of Fishery Processing Technology Department and a student; (2) setting, it includes the placeand process of teaching, learning, involving teachers and students; (3) document. The data weregathered with the techniques of 1) interview, 2) analyze document, and 3) observations. The datawere, then, analyzed inductively with steps of data reduction, presentation of data and conclusionsand also verifying. The data were validated with the techniques of triangulation and reviewinformation. The research partnership management of World of Enterprises and Industry with FisheryProcessing Technology Department of vocational school 1 Sanden Bantul program is done as wellshowed that (a) the planning: to decide World of Enterprises and Industry, to make MoU, to do workexperience for students, to synchronize the subjects learnt in school with practical work in World ofEnterprises and Industry, (b) organizing:to maximize the school resources to reach the goal throughschool organization, (c) actuating: to prepare source of fund, infrastructure, giving studentsknowledge and skill to fulfill standard and need of World of Enterprises and Industry, (d) controlling:to monitor and evaluate the partnership program and its supporting factors including human andnonhuman resources. Meanwhile, the obstacles of the program are location, transportation and workexperience fund.